2014
DOI: 10.3791/51442
|View full text |Cite
|
Sign up to set email alerts
|

Network Analysis of the Default Mode Network Using Functional Connectivity MRI in Temporal Lobe Epilepsy

Abstract: Functional connectivity MRI (fcMRI) is an fMRI method that examines the connectivity of different brain areas based on the correlation of BOLD signal fluctuations over time. Temporal Lobe Epilepsy (TLE) is the most common type of adult epilepsy and involves multiple brain networks. The default mode network (DMN) is involved in conscious, resting state cognition and is thought to be affected in TLE where seizures cause impairment of consciousness. The DMN in epilepsy was examined using seed based fcMRI. The ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 42 publications
4
24
0
Order By: Relevance
“…In addition, the pattern of WM diffusivity alterations found in our sample group could play a significant role in the widespread decrease in connectivity found in MTLE patients (Englot et al, 2015, Haneef et al, 2014, Voets et al, 2012). Previous studies have reported decreased connectivity in MTLE in bilateral posterior temporal and parieto-occipital cortices, perisylvian region, lateral and medial frontal neocortex, posterior cingulum/precuneus and insular cortex (Englot et al, 2015, Haneef et al, 2014, Voets et al, 2012).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…In addition, the pattern of WM diffusivity alterations found in our sample group could play a significant role in the widespread decrease in connectivity found in MTLE patients (Englot et al, 2015, Haneef et al, 2014, Voets et al, 2012). Previous studies have reported decreased connectivity in MTLE in bilateral posterior temporal and parieto-occipital cortices, perisylvian region, lateral and medial frontal neocortex, posterior cingulum/precuneus and insular cortex (Englot et al, 2015, Haneef et al, 2014, Voets et al, 2012).…”
Section: Discussionmentioning
confidence: 64%
“…Previous studies have reported decreased connectivity in MTLE in bilateral posterior temporal and parieto-occipital cortices, perisylvian region, lateral and medial frontal neocortex, posterior cingulum/precuneus and insular cortex (Englot et al, 2015, Haneef et al, 2014, Voets et al, 2012). The decrease in connectivity may account for the deleterious effects of epilepsy including gray matter atrophy, cortical hypometabolism, neuropsychological deficits, and cognitive impairment (Thom, 2014).…”
Section: Discussionmentioning
confidence: 90%
“…Several studies have reported disrupted functional connectivity in resting-state functional connectivity in patients with epilepsy (Englot et al, 2015, Haneef et al, 2014a, Luo et al, 2011, Maneshi et al, 2014, Voets et al, 2012). More specifically, works employing the complex network analysis approach have shown increased characteristic path lengths (Horstmann et al, 2010, Chiang and Haneef, 2014, Otte et al, 2012, Vlooswijk et al, 2011) in epilepsy in fMRI as well as in white matter studies, which is in alignment with our results, and confirms the overall disruption of functional connectivity.…”
Section: Discussionmentioning
confidence: 99%
“…Even though many studies have shown disruptions in brain connectivity caused by epilepsy (Englot et al, 2015, Haneef et al, 2014a, Luo et al, 2011, Maneshi et al, 2014, Voets et al, 2012), the mechanisms by which the subcortical structures are related to the cortical epileptic processes are largely unknown. We hypothesize that the BG-thalamic system might modulate large scale cortical networks and this modulation might be disturbed in epilepsy.…”
Section: Introductionmentioning
confidence: 99%
“…Resting-state studies have described functional connectivity abnormalities in several cognitive networks in epilepsy such as the well known default-mode network (DMN) [30,31], and its subdivisions [32], in addition to attentional [33], language [34,35], and visuospatial working memory [36] networks putting at risk a wide range of neurocognitive and affective functions.…”
Section: Resting-state Functional Connectivity Reveals Neurocognitivementioning
confidence: 99%